2017
DOI: 10.1007/s11678-017-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

Rekonstruktion anteromedialer Humeruskopfimpressionsfrakturen mit knöchernen Auto- oder Allografts

Abstract: Mit einer Häufigkeit von 2-3 % aller Schulterluxationen ist die traumatische hintere Luxation eine selten vorkommende Verletzung des Schultergürtels, welche initial leicht übersehen werden kann [1]. Eine zeitlich verzögerte Diagnosestellung kann einen nicht unbedeutenden Einfluss auf eine evtl. notwendige chirurgische Intervention mit sich ziehen. Lässt sich eine traumatische hintere Schulterluxation nativradiologisch und klinisch nicht eindeutig ausschließen, sollte eine zeitnahe bilaterale Computertomographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Our results support this argument, as the average measured gamma angle was 105°, and all measured gamma angles were 90°o r higher. Similarly, Knierzinger et al reported five patients with an RHSL with gamma angles between 84.6°and 141.7°w ho were treated surgically by segment reconstruction via allo-or autograft [44]. The range of beta angles between -20°a nd 70°demonstrates the variability in location of the RHSL, but the relatively small average beta angle of 30°underlines that in most cases the RHSL can be found in close proximity to the bicipital groove of the long head of the biceps, which is located at 0°.…”
Section: Impression Type Fractures (Rhsl)mentioning
confidence: 95%
“…Our results support this argument, as the average measured gamma angle was 105°, and all measured gamma angles were 90°o r higher. Similarly, Knierzinger et al reported five patients with an RHSL with gamma angles between 84.6°and 141.7°w ho were treated surgically by segment reconstruction via allo-or autograft [44]. The range of beta angles between -20°a nd 70°demonstrates the variability in location of the RHSL, but the relatively small average beta angle of 30°underlines that in most cases the RHSL can be found in close proximity to the bicipital groove of the long head of the biceps, which is located at 0°.…”
Section: Impression Type Fractures (Rhsl)mentioning
confidence: 95%